Modeling of Wind Power Plant with Doubly-Fed Induction Generator - Syahputra, Ramadoni; Soesanti, Indah (Journal of Electrical Technology UMY, 2017)
This paper presents the modeling and simulation of wind turbine driven by doubly-fed induction generator which feeds ac power to the distribution network. A stator flux oriented vector control is used for the variable speed doubly-fed induction generator operation. By controlling the generator excitation current the amplitude of the stator EMF is adjusted equal to the amplitude of the grid voltage. To set the generator frequency equal to the grid one, the turbine pitch angle controller accelerates the turbine/generator until it reaches the synchronous speed. The system is modeled and simulated in the Matlab Simulink environment in such a way that it can be suited for modeling of all types of induction generator configurations. The model makes use of rotor reference frame using dynamic vector approach for machine model. The system is also simulated when a fault occurs in 25 kV grid of distribution system. The results of a single line to ground fault and a symmetrical three-phase ground fault is analyzed. The results show that the wind energy conversion system can normally operate in fault conditions.